Pre-treatment serum vitamin D deficiency is associated with increased inflammatory biomarkers and short overall survival in patients with pancreatic cancer. (February 2021) - Rasmussen, Louise S.; Yilmaz, Mette K.; Falkmer, Ursula G.; Poulsen, Laurids Ø.; Bøgsted, Martin; Christensen, Heidi S.; Bojesen, Stig E.; Jensen, Benny V.; Chen, Inna M.; Johansen, Astrid Z.; Hansen, Carsten P.; Hasselby, Jane P.; et al.
Abstract: Background: Vitamin D deficiency and inflammation are associated with increased mortality. We investigated the relationship between pre-treatment serum vitamin D levels, inflammatory biomarkers (IL-6, YKL-40 and CRP) and overall survival (OS) in pancreatic ductal adenocarcinoma (PDAC) patients. Methods: Pre-treatment serum vitamin D, IL-6, YKL-40 and CRP levels were determined in 1, 267 patients with PDAC enrolled from July 2008 to September 2018 in the prospective BIOPAC study (NCT03311776). The patients were grouped according to vitamin D levels: sufficient >50 nmol/L, insufficient 25–50 nmol/L and deficient <25 nmol/L. Results: Across all tumour stages, vitamin D-deficient patients had the highest median levels of IL-6 (8.3 pg/mL, range 0.7–91), YKL-40 (177 ng/ml, range 25–5279) and CRP (15.5 mg/L, range 0.8–384). The resected stage I and II patients with vitamin D deficiencies had a shorter median OS, 18.3 months (95% CI, 12.1–31.5 months) than those with sufficient levels, 29.7 months (95% CI, 22.3–36.1 months), and the hazard ratio for death was 1.55 (95% CI, 1.04–2.31; p = 0.03). In advanced PDAC, there was no significant difference in OS between the vitamin D groups. Conclusions: Vitamin D deficiency was associated with increased inflammatory biomarkers in all PDAC stages. The resected stage I and II patients with sufficient vitamin D levels had a higher OS than those with a vitamin D deficiency. However, there was no correlation between vitamin D levels and survival in advanced PDAC. Future studies need to investigate vitamin D supplementation effects on survival in PDAC. Highlights: Pre-treatment vitamin D was associated with inflammatory biomarkers in PDAC. Vitamin D deficiency was associated with increased levels of IL-6, YKL-40 and CRP. Vitamin D deficiency yielded a short survival in patients with early stage. Vitamin D deficiency did not influence survival in patients with advanced stage.